To T or not to T: Differences in Testosterone Use and Discontinuation by HIV Serostatus among Men who Have Sex with Men1. Issue 9 (10th July 2018) - Haberlen, SA; Jacobson, LP; Palella, FJ; Dobs, A; Plankey, M; Lake, JE; Kingsley, LA; Stall, R; Post, WS; Brown, TT
Abstract : Objectives: The aim of the study was to characterize contemporary patterns and correlates of testosterone therapy (TTh) use and discontinuation by HIV serostatus among men in the Multicenter AIDS Cohort Study (MACS). Methods: Self‐reported testosterone use data were collected semiannually from 2400 (1286 HIV‐infected and 1114 HIV‐uninfected) men who have sex with men. Multivariable Poisson regression was used to estimate prevalence ratios for TTh use and predictors of TTh discontinuation (2012–2015). Results: Use was higher among HIV‐infected compared with HIV‐uninfected men in all age strata, with an age‐adjusted prevalence of 17% vs . 5%, respectively (adjusted prevalence ratio 3.7; P < 0.001). Correlates of use in the multivariable model were similar by HIV serostatus: white race, the Los Angeles (LA) site, more than one recent sexual partner, non‐smoking status, and higher American Heart Association/American College of Cardiology (AHA/ACC) cardiovascular disease (CVD) risk score category (approximately 70% of testosterone users were in the high‐risk category). Compared with HIV‐uninfected men, HIV‐infected men more frequently reported building muscle mass as a motivation for testosterone use. The TTh discontinuation rate was 20.9/100 person‐years [95% confidence interval (CI) 17.3, 25.0/100 person‐years]. Relative to HIV‐uninfected men, HIV‐infected men were half as likely to discontinue (adjusted incidence rate ratio 0.4; P < 0.001). Discontinuation was 40% higher in the period after the US Food and Drug Administration (FDA) safety communication for testosterone in 2014, independent of co‐factors ( P = 0.06). Conclusions: Given the high prevalence of both TTh use and CVD risk among HIV‐infected men, the benefits and risks of TTh should be examined in future studies of aging HIV‐infected men and monitored routinely in clinical practice.